Learning processes in pre-service teacher training for secondary school mathematics teachers (2009)
In this paper, I present research in which I explore the learning processes of the future teachers who participated in a secondary mathematics methods course. I introduce the notion of didactic analysis as a conceptualisation of the activities that a teacher should perform in order to design, implement and assess didactic units. I specify the idea of didactic knowledge as the knowledge required to perform didactic analysis. Based on four related studies, I describe and characterise the future teachersÕ development of didactic knowledge by establishing four developmental stages of their didactic knowledge and characterising, from several view-points, the evolution of the meanings that the future teachers constructed throughout the course. The results of these studies reveal several aspects of the complexity involved in the training of future teachers of secondary school mathematics. They show the need to study further the design and development of this kind of program and to take into account the role that the trainers can play in the learning of future teachers.